Job-related stress, school climate and burnout among classroom teachers - Balian Sarkissian, Takouhie (Beirut Haigazian University - Faculty of Social & Behavioral Sciences - Department of Education, 2001)
A questionnaire-based research was conducted to examine the relationship between both forms of teacher burnout (psychological and physical) with the following factors: (a) job-induced stress, (b) school climate and (c) teaching experience. The questionnaire was adopted from Hock (1988) and Riehl and Sipple (1996). The sample was composed of 48 elementary English teachers of private schools in Beirut. The results showed that only the school climate was positively related with both forms of burnout. Moreover, it was found that buffers (i.e. parental support, paperwork and being provided with the necessary teaching materials) were significantly related with teachers' physical burnout. While the order of students (i.e. students' attitude toward school work and their behavior in classroom) and administrative support were significantly correlated with teachers' psychological burnout. Salary was also found to be the highest stress-inducing factor among the other job-stressors, for most of these teachers. Therefore, to enhance the psychological and physical well-being of teachers, they should be supported by their principals and by their students' parents. In addition, they should be provided with the essential teaching materials and be relieved from unnecessary paperwork and from the disciplinary problems that are associated with students.
: Mémoire
Keywords: Climat scolaire; Epuisement Psychologique; Les Attitudes et conceptions des enseignants; Psychological Burnout; Teachers attitudes and conceptions School Climate